Strategi Dakwah Memberantas Judi Online di Indonesia - Mastori, Mastori; Anang, Moh. Sitoh; Maskur, Asep; Safar, Karmuji Abu (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2024)
Theologically, gambling is an immoral act that is forbidden by Islam and is a major sin. Likewise, in the legal system of the Republic of Indonesia, gambling is categorized as a criminal act. Even so, the facts show that millions of Indonesians can still access gambling sites and get involved in these illegal games. This condition is very worrying because the practice of online gambling can definitely damage the order of people's lives, both in the theological and sociological aspects. This research uses a qualitative descriptive method to understand the facts of online gambling in depth. Data was collected using documentation methods from various sources such as the Koran, books, journals, online news and laws and regulations related to the research object. The research results show that there are three strategies for preaching to eradicate online gambling, namely: First, a theological normative approach, namely by instilling an understanding of the prohibition and dangers of online gambling. This strategy can be used in fardhiah or mass da'wah, such as in tabligh akbar or recitation activities. Second, the educational approach involves the active role of teachers as preachers in the school environment. Individually, each teacher should be able to touch on gambling material in each lesson. Institutionally, schools can create a special curriculum that emphasizes awareness of the dangers of online gambling and activates the activities of school da'wah institutions. Third, the technological approach. Da'i can use da'wah strategies in the form of using digital media to spread anti-gambling content and develop alternative media platforms that are positive for society.